2022
DOI: 10.30782/jrvm.1025604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Egg Quality Characteristics of Different Quail Lines

Abstract: This study was carried out to investigate external and internal egg quality traits of different quail lines housed in a multitier cage system. The study was performed on eggs of three different lines of quail as wild type, recessive white and black cross-line stock raised for commercial production. All flocks in the experiment were housed in same environmental conditions for quail and fed same diets during the experiment. A total of 60 eggs from each quail lines were used to determine internal and external egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Finally, the eggshell percentage differed significantly (p<0.01) among the studied lines, where the previous trend was absent, because the highest value was recorded for White Local and the lowest one was for Dark Ukraine eggs, while both other lines were intermediate; this result may be attributed to its shell thickness. However, similar results were found by [19] and [20] for the superiority of European lines over local ones. Shell thickness appeared to record the significant (p<0.01) superiority for the dark Ukrainian line compared to others, and both local lines had the same value (0.31) mm.…”
Section: Comparison Among European and Asiatic Lines For Egg Qualitysupporting
confidence: 85%
“…Finally, the eggshell percentage differed significantly (p<0.01) among the studied lines, where the previous trend was absent, because the highest value was recorded for White Local and the lowest one was for Dark Ukraine eggs, while both other lines were intermediate; this result may be attributed to its shell thickness. However, similar results were found by [19] and [20] for the superiority of European lines over local ones. Shell thickness appeared to record the significant (p<0.01) superiority for the dark Ukrainian line compared to others, and both local lines had the same value (0.31) mm.…”
Section: Comparison Among European and Asiatic Lines For Egg Qualitysupporting
confidence: 85%
“…Ahmed, (2021); Ahmed and AL-Barzinji, (2022) detected that there was a significant genetic difference in productive traits among the three lines of Kurdish quail. Petek et al, (2022) observed significant differences among quail breeds for HD percentage as the wild breed produced the highest HD percentage and heavier eggs than the other breeds. On the other hands, absence of any effects of quail breed on HD percentage, reported when compared four different (black, brown, desert and white) breeds of Japanese quail (Ibrahim et al, 2022).Hen-day egg production (%) results affected by adding Lcarnitine (LC) in different lines of local quail are presented in Table (3).…”
Section: Hen Day Egg Production (Hd%)mentioning
confidence: 87%
“…Several researchers stated that there were significant variations among genotypes and lines in egg weight traits, Ahmed and AL-Barzinji, (2020) found significant differences in the variance lines of the quail eggs' weight. Petek et al, (2022) compared three different Japanese quail (wild, white and black) they were observed that wild quail egg weight was significantly heavier than the other quail lines. Hamad and AL-Barzinji, (2023) evaluated three Kurdish quail breeds (desert, brown and white) showed the white breed was significantly superior to other breeds in EW.…”
Section: :1: Egg Weight Traitsmentioning
confidence: 99%
“…Moreover, Cahyadi et al (2019) found that the eggs of the brown plumage quail line possessed superior external and internal characteristics compared to the eggs of the black plumage line. Petek et al (2022), however, found that eggs from the cross-line black coloured quail line are heavier and possess higher breaking strength compared to the eggs of the wild-type and recessive white quail lines. They also determined that eggs from the white line of quails had a shorter egg length and the highest shape index values, along with a lighter egg yolk color.…”
Section: Introductionmentioning
confidence: 90%